Level of Physical Activity and Its Associated Factors Among Type II Diabetes Patients in Dessie Referral Hospital, Northeast Ethiopia - Edmealem A (Dove Medical Press, 2020)
Afework Edmealem, Sewunet Ademe, Belachew Tegegne Department of Nursing, School of Nursing and Midwifery, Wollo University, Dessie, EthiopiaCorrespondence: Afework Edmealem Tel +251921287207Email afeworkyalem@gmail.comBackground: Overweight and obesity results in poor control of chronic illnesses such as diabetes mellitus. The main reason for being overweight and obese among patients with chronic illness is low level of physical activity. Thus, this study aimed to assess level of physical activity and its associated factors among type II diabetes patients at Dessie Referral Hospital, Northeast Ethiopia.Methods: A hospital-based cross-sectional study was employed from October 1 to November 25 2019 in Dessie Referral Hospital. The study utilized systematic sampling technique to recruit the sample population of 364 diabetic patients. Face-to-face exit interview was used to collect the data. The data were presented with text and tables. Bivariable and multivariable binary logistic regression was employed to identify independent predictors of low level of physical activity at a P-value of < 0.05.Results: From the total study participants, 110 (33.1%) of them did not perform health enhancing physical activity. Patients whose body mass index was below 18.5 kg/m2 did not perform health enhancing physical activity twice more likely compared with patients whose weight was normal (AOR=2.36, 95%CI: 0.02– 5.42). Patients who were depressed did not perform health enhancing physical activity five times more likely compared with their counterparts (AOR=4.83, 95%CI: 1.46– 15.96). In addition, being widowed (P=0.037), living in an urban area (P=0.028) and duration of disease (P=0.020) were statistically associated with low level of physical activity.Conclusion and Recommendations: The level of physical activity among patients with type II diabetes was low. Being widowed, living in an urban area, being underweight, duration of disease and being depressed were independent predictors of low level of physical activity. Health education should be given in every visit to patients with type II diabetes. Promotion of physical activity through campaign should be done.Keywords: physical activity, factors, Ethiopia